PENGARUH PERBEDAAN KONSENTRASI KALSIUM KARBONAT (CaCO3) TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK SEREAL SARAPAN BERAS HITAM-PISANG RAJA - Jaya, Yohan Adi; Suseno, Thomas Indarto Putut; Jati, Ignasius Radix Astadi Praptono (Jurnal Teknologi Pangan dan Gizi, 2018)
One of the cereal varieties which is potentially processed to be a breakfast cereal is black rice. Black rice (Oryza sativa L. indica) is one of the rice varieties commonly grown in Indonesia. The usage of banana (Musa paradisiaca var sapientum) is to improve the taste and aroma of the cereal and also to utilize Indonesia’s local commodity. Ca2+ ions from calcium carbonate (CaCO3) can interact with cereal starch granules and affects the starch gelatinization. The usage level of CaCO3 is 0,00%; 0.10%; 0.20%; 0.30%; 0.40%; 0.50%; and 0.60%. The observed parameters are moisture contents, rehydration rate, water absorption capacity, water activity (aw), texture, colour, and organoleptic properties. Total anthocyanin content, antioxidant activity, and resistant starch content are observed only in the best CaCO3 usage level. The result are analyzed using ANOVA (Analysis of Variance) test with α = 5% to determine whether there is a significant difference or not. If there is a significant difference, the analysis is continued with DMRT (Duncan’s Multiple Range Test) using α = 5%. The study result shows that have moisture contents 2.11-3.36%; rehydration rate at temperature 30oC 0.1121-0.2338 g water/s, temperature 40oC 0,1550-0,3033 g water/s, temperature 50oC 0,1870-0,3626 g water/s, temperature 60oC 0,2463-0,4507 g water/s, temperature 70oC 0,3104-0,5532 g water/s, temperature 80oC 0,3827-0,6533 g water/s, water absorption 82.02-125.18%; capacity water activity (aw) 0.35-0.40; texture for hardness 632.046–916.937g dan for cripsness 0.020–0.041cm-1; and the colour conclusion is red purple. The best CaCO3 usage level from organoleptic tests is 0.60%. The total anthocyanin content is 2.2722mg/100mL; the antioxidant activity is 87.46%; and the resistant starch content is 19.753 %.